The effectiveness of reading aloud strategies on literal reading comprehension, reading proficiency and text level difficulties - Muhammad Khalid, Mehmood Sajid (2022)
Reading aloud is an important learning strategy that can boost the consistency of the reading comprehension skills of students, which can enable them to overcome the challenges of high-level instructional materials. Due to poor school English standards, Saudi students enter at university level with a weak reading background and to fill the gap there was need to investigate for which this research study was conducted. The purpose of this study is to investigate the impact of using Reading Aloud Strategies (RAS) on low reading proficiency Saudi students’ literal reading comprehension skills and reading proficiency against text level difficulties. The ability to comprehend information and facts that are clearly expressed in the text is referred to as literal reading comprehension. It is the basic level of reading comprehension. A number of reasons, including a lack of word reading, vocabulary, reading expertise, and the reader's ability to create meaning from the text of learning material are referred to as text level difficulty. This study employed a mixed-method design with triangulation approach. Three research instruments were administered in the study: a reading comprehension test, a student questionnaire, and an interview protocol for teachers and students. SPSS software was used to analyse the quantitative data analysis, and Atlas t.i8 was used to analyse the qualitative data. The participants comprised 100 first year students at a college level English taking reading course at an English Language Centre of King Faisal University, Saudi Arabia. Fifty (50) students were assigned into an experimental group where the strategies of reading aloud were applied, and silent reading strategies were used in the control group with fifty (50) students as well. The experimental results were significant on literal reading comprehension skills, and reading proficiency as the p value was below 0.5., and the correlation was significant at the 0.05 level (2-tailed). The reading comprehension test utilised high-level text in the reading passages adhering to the administrative guideline of the university. The findings of the reading comprehension test show that the gain score of Silent Reading Strategies (control group) was 3% and RAS was 17% (experimental group). There was a difference of 14%, but it was not a high growth on text difficulty. In addition, findings of the student questionnaire and (30) students’ interview protocol revealed majority of the students believed that RAS worked effectively to improve their literal reading comprehension skills and reading proficiency. The results of the teacher interview protocol also revealed that they had the same opinion similar to the student. However, through the interview protocol data, the students believed that RAS could help them to understand higher level text difficulties whereas the teachers thought RAS were not effective on the difficult texts. Therefore, there is a significant contribution of using RAS to assist low proficiency Saudi students when difficult texts are used as instructional materials, and this should be further investigated. It is recommended that Saudi students use Reading Aloud Strategies meaningfully, and these strategies may be implemented in future studies. There is a continuing need for RAS research-based protocols, ideally in the Alhasa region. It also recommended that investigation on RAS in among Saudi students is carried out comparing students of different gender. To compare results, the analysis could also be extended to other EFL environments. The study was confined to one provincial institution in the province of Alhasa. Further research is also required at Master level for the use of RAS by Saudi students for text level challenges as master level students are also weak in reading comprehension skills having text difficulties.